Staufen Recruitment into Stress Granules Does Not Affect Early mRNA Transport in Oligodendrocytes - Thomas, Maria Gabriela (2004)
Staufen is a conserved double-stranded RNA-binding protein required for mRNA localization in Drosophila oocytes and embryos. The mammalian homologues Staufen 1 and Staufen 2 have been implicated in dendritic RNA targeting in neurons. Here we show that in rodent oligodendrocytes, these two proteins are present in two independent sets of RNA granules located at the distal myelinating processes. A third kind of RNA granules lacks Staufen and contains major myelin mRNAs. Myelin Staufen granules associate with microfilaments and microtubules, and their subcellular distribution is affected by polysome-disrupting drugs. Under oxidative stress, both Staufen 1 and Staufen 2 are recruited into stress granules (SGs), which are stress-induced organelles containing transiently silenced messengers. Staufen SGs contain the poly(A)-binding protein (PABP), the RNA-binding proteins HuR and TIAR, and small but not large ribosomal subunits. Staufen recruitment into perinuclear SGs is paralleled by a similar change in the overall localization of polyadenylated RNA. Under the same conditions, the distribution of recently transcribed and exported mRNAs is not affected. Our results indicate that Staufen 1 and Staufen 2 are novel and ubiquitous SG components and suggest that Staufen RNPs are involved in repositioning of most polysomal mRNAs, but not of recently synthesized transcripts, during the stress response.